2014
DOI: 10.1111/1750-3841.12651
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soaking with Natural Additives in Combinations with Vacuum or Modified Atmosphere Packaging on Microbial Populations and Shelf Life of Fresh Truffles (Chinese Tuber Indicum)

Abstract: The objective of this study was to evaluate the relative effects and interactions of combined soaking treatment using citric acid (CTA) and apple polyphenol (APP) at mild heating temperatures for the inactivation of the external and internal microflora (mesophilic aerobic bacteria, mesophilic anaerobic bacteria, and fungi) in Chinese Tuber indicum, as well as to analyze the microbiological and sensory changes under modified atmosphere packaging (MAP)- and vacuum atmosphere packaging (VAC)-packed Chinese T. ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Each microbial count (expressed as log CFU/g) was calculated based on the mean of three samples. 29 Ten bacterial colonies on the respective agar (except Bacillus colonies which were below the quantification limit) were isolated and tested for oxidase and catalase reactions 30,31 before they were Gram-stained (Fluka, Australia). 6,32,33 Spore staining was performed for Bacillus spp.…”
Section: Microbiological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Each microbial count (expressed as log CFU/g) was calculated based on the mean of three samples. 29 Ten bacterial colonies on the respective agar (except Bacillus colonies which were below the quantification limit) were isolated and tested for oxidase and catalase reactions 30,31 before they were Gram-stained (Fluka, Australia). 6,32,33 Spore staining was performed for Bacillus spp.…”
Section: Microbiological Analysismentioning
confidence: 99%
“…6 The variations in the microbial counts between studies could be due to differences in collection season, maturity, origin, geographical location, soil microbiology, and postharvest packaging. 29,37,38 Pseudomonadaceae are psychrotrophic (cold-tolerant) bacteria that can proliferate even at 2-5 C [39][40][41] and can contribute to food spoilage particularly in food with a high water activity. 42,43 Sorrentino et al 8 reported that Pseudomonas spp.…”
Section: Pseudomonas Sppmentioning
confidence: 99%